Kebiasaan Menonton Mukbang dan Perilaku Emotional Eating serta Kaitannya dengan Status Gizi Mahasiswa Universitas PGRI Yogyakarta: Mukbang Video Exposure, Emotional Eating, and Its Relationship with Nutritional Status among University Students - Doloksaribu, Susi Susanti; Fayasari, Adhila (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2025)
Mukbang is a video show featuring someone consuming large amounts of food, and it has now become a popular phenomenon among the public, especially young adults. This show has the potential to influence food consumption behaviour and impact nutritional status. Additionally, emotional eating behaviour is known to influence energy intake and nutritional balance in individuals. This study aims to analyse the relationship between the habit of watching mukbang videos and emotional eating behaviour with nutritional status among students at PGRI University Yogyakarta. This study used a quantitative cross-sectional design with 410 active students as respondents. Data were collected using the Mukbang Addiction Scale (MAS) and Dutch Eating Behaviour Questionnaire (DEBQ) distributed. Nutritional status was determined based on body mass index (BMI), and relationship analysis was conducted using Fisher’s Exact test. The results showed that 61.0% of respondents had normal nutritional status, 32.4% were overweight, and 6.6% were underweight. Furthermore, there was a significant association between the habit of watching mukbang videos and nutritional status (p<0.05), as well as between emotional eating behaviour and nutritional status (p<0.05). These findings highlight the importance of education on the influence of food-related content and emotional management as part of efforts to maintain a balanced nutritional status.